Volar Dislocation of the Fourth and Fifth Carpometacarpal Joint Associated with Hamate Hook Fracture: A Case Report and Literature Review - Natsumi Saka; Hirotada Matsui; Hideki Tsuji (Case Reports in Orthopedics)
We report a case of volar fourth and fifth carpometacarpal (CMC) joint dislocation complicated by a hamate hook fracture. The CMC joint was reduced in a closed fashion and temporally fixed with Kirschner wires. Using intraoperative computed tomography, the displaced fracture of the hamate hook was reduced by open reduction and internal fixation and fixed with a screw. We suggest that this rare injury was caused by the over contraction of the flexor carpi ulnaris and avulsion force from the ligamentous structure around the pisiform, hamate, and metacarpal bones.